LPCAT3 regulates the proliferation and metastasis of serous ovarian cancer by modulating arachidonic acid - Fang Wen; Hongjian Ling; Rui Ran; Xinya Li; Houmei Wang; Qianfen Liu; Min Li; Tinghe Yu (Translational Oncology)
Background: Lysophosphatidylcholine acyltransferase 3 (LPCAT3) promotes ferroptosis through the incorporating polyunsaturated fatty acids into membrane phospholipids, however, its role in serous ovarian cancer remains unclear. Here explored cancer proliferation and metastasis after modulating LPCAP3. Methods: LPCAT3 protein in ovarian cancer tissues was detected using bioinformatic and immunohistoche mical assays. Cell behaviors were observed after up- or down-regulating LPCAT3. Lipid metabolites were determined, and then the pathway enrichment analysis was performed. Results: The expression level of LPCAT3 in serous ovarian cancer tissues was lower than that in other types of ovarian cancer, and high expression was associated with a longer survival time. Overexpressing LPCAT3 reduced cell proliferation, migration and invasion via enhancing ferroptosis and decreasing the survival signaling; these behaviors were enhanced in LPCAT3-downknocked cells, where a higher abundance of arachidonic acid was observed followed by up-regulation of the downstream survival signaling. In vivo, up-regulation of LPCAT3 decreased tumor growth, but down-regulation enhanced tumor growth and metastasis. Conclusions: LPCAT3 modulated metabolism of arachidonic acid, thereby regulating ferroptosis and the survival signaling to determine cancer growth and metastasis.